O ensino da percepção musical para iniciantes, com ênfase na utilização de timbres alternativos e no uso da palavra para uma turma de graduação em pedagogia - Goiânia - Go - Sousa, Jairo Aurélio de Deus (2015)
This work aimed to develop a methodological proposal to the teaching of Musical Perception for education students. The proposal musical experience was developed and implemented with a graduating class in Pedagogy. This is an Action Research carried out in the Faculdade Padrão in Goiânia- GO. It began with a literature review, developed experiences with groups and even data that were analyzed. At first, we opted for the realization of a pilot project, through which it gave 12 sessions, classes, whose results were included in this study, aimed at consolidating the proposed methodology. Finished this time of the study, there was 11 new sessions-classes, in order to demonstrate, through filming and recorded protocols, the embodiment of the proposal / consolidated methodology, procedures of each session and the results of the teaching / learning. Data collection was made by 5 collection instruments: 1 - Protocols; 2 - Two tests at the beginning and end of the study, called Pre-test and Post-test; 3 - Interviews, made to research participants; 4 - Footage of classes; and 5 - Jury Analysis Results. The hypothesis of the research was that it would be possible to answer the following questions described; once the analysis of data collected: 1 - How to relate and evaluate a variety of textbooks within an alternative proposal for the teaching of rhythmic and melodic perception ?; 2 - How to insert the use of compositions created by the researcher, in the teaching of Musical Perception ?; 3 - How to operationalize the use of alternative sounds and words as significantly relevant aspects in the learning of Musical Perception ?; and 4 - How to adjust the teaching methodology proposal, given that the target audience will be students / of the undergraduate degree in Pedagogy? To support the theoretical reflections and the data collected during the action research, we used theoretical basis of the authors Bellochio (2000), Schafer (1991), Brito (2003) e Swanwick (2003); beyond the analysis of official documents defining the guidelines for Early Childhood Education. It was concluded that the production of a contextualized material having a musical experience as a major feature, allows the music educator build pathways that can promote an enriching music education.